Isolation, one-step affinity purification, and characterization of a polyextremotolerant laccase from the halophilic bacterium Aquisalibacillus elongatus and its application in the delignification of sugar beet pulp. (April 2017) - Rezaei, Shahla; Shahverdi, Ahmad Reza; Faramarzi, Mohammad Ali
Graphical abstract: Highlights: A laccase producing halophile Aquisalibacillus elongatus was bio-prospected. Rapid and efficient purification was achieved using a synthetic affinity resin. Purified laccase was an extremely stable against pH, temperature, and additives. The laccase had exceptionally specificity to a wide range of potential substrates. Enzymatic hydrolysis in [BMIM][PF6 ] yielded 78.4% delignification within 12 h. Abstract: The aim of the present work was to study the ability of a halophilic bacterial laccase to efficient delignification in extreme conditions. Here, a highly stable extracellular laccase showing ligninolytic activity from halophilic Aquisalibacillus elongatus is described. The laccase production was strongly influenced by NaCl and CuSO4 and under optimal conditions reached 4.8 U mL −1 . The monomeric enzyme of 75 kDa was purified by a synthetic affinity column with 68.2% yield and 99.8-fold purification. The enzyme showed some valuable features viz. stability against a wide range of organic solvents, salts, metals, inhibitors, and surfactants and specificity to a wide spectrum of substrates diverse in structure and redox potential. It retained more than 50% of the original activity at 25–75 °C and pH 5.0–10.0. Furthermore, the enzyme was found to be effective in the delignification of sugar beet pulp in an ionic liquid that makes it useful for industrial applications.